Waterproof sealing layer for sealing microcells of electro-optical devices
Patent Information
- Application Number
- CN202380020946.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-08
- Filing Date
- 2023-04-06
- Publication Date
- 2024-12-13
AI Technical Summary
The existing sealing layers have shortcomings in waterproofing and blocking non-polar fluids, especially when exposed to water, making it difficult to maintain the sealing properties and properties of the electrophoretic medium.
A combined sealing layer of polyvinyl alcohol and polyurethane is used, wherein the polyvinyl alcohol contains acetoacetate functional group in the molecular structure, and the polyurethane has a high peak melting temperature and crystallinity index. The aqueous sealing composition formed is used to seal the micro-units of the electrophoretic display. .
It achieves good waterproofness and non-polar fluid barrier properties, extends the service life of the sealing layer, and improves the performance stability of the electro-optical display.
Smart Images

Figure CN118891322A8_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 329,066, filed on April 8, 2022, which is incorporated by reference in its entirety along with all other patents and patent applications disclosed herein. Field of the Invention
[0003] The present invention relates to a sealing layer for sealing micro-units of electro-optical devices. The sealing layer comprises a combination of polyurethane and polyvinyl alcohol, the polyvinyl alcohol containing acetoacetate functional groups in its molecular structure. The sealing layer is waterproof and shows good barrier properties to non-polar fluids. Background of the Invention
[0005] The term "electro-optical" as applied to a material or display is used herein in its conventional sense in the imaging arts to refer to a material having a first display state and a second display state that differ in at least one optical property, the material changing from its first display state to its second display state by application of an electric field to the material. While the optical property is typically a color perceptible to the human eye, it may be another optical property such as optical transmission, reflection, luminescence, or, in the case of a display intended for machine reading, a false color in the sense of a change in reflectivity of electromagnetic wavelengths outside the visible range.
[0006] The terms "bistable" and "bistability" are used herein in their conventional sense in the art to refer to a display that includes display elements having first and second display states that differ in at least one optical property, and such that after any given element has been driven to assume its first or second display state by means of an addressing pulse of finite duration, that state will persist after termination of the addressing pulse for at least several times, e.g., at least four times, the minimum duration of the addressing pulse required to change the state of the display element. Some particle-based electrophoretic displays with grayscale capability are shown in U.S. Pat. No. 7,170,670 to be stable not only in their extreme black and white states, but also in their intermediate gray states, and some other types of electro-optical devices are likewise. This type of display is properly referred to as "multistable" rather than bistable, but for convenience, the term "bistable" may be used herein to cover both bistable and multistable displays.
[0007] One type of electro-optical device that has been the subject of intensive research and development for several years is a particle-based electrophoretic display, in which a plurality of charged particles move through a fluid under the influence of an electric field. When compared to liquid crystal displays, electrophoretic displays may have the properties of good brightness and contrast, wide viewing angles, state bistability, and low power consumption.
[0008] Many patents and applications assigned to or under the names of the Massachusetts Institute of Technology (MIT), E Ink Corporation, E Ink California, LLC and related companies describe various technologies for encapsulated and microcell electrophoretic media and other electro-optical media. Encapsulated electrophoretic media contain a plurality of small capsules, each of which itself includes an inner phase containing particles that electrophoretically move in a fluid medium, and a capsule wall surrounding the inner phase. Typically, the capsules themselves are held in a polymer binder to form a coherent layer between two electrodes. In a microcell electrophoretic display, the charged particles and fluid are not encapsulated in microcapsules, but are retained in a plurality of cavities formed in a carrier medium, which is typically a polymer film.
[0009] The technologies described in these patents and applications include:
[0010] (a) electrophoretic particles, fluids, and fluid additives; see, e.g., U.S. Pat. Nos. 7,002,728 and 7,679,814;
[0011] (b) capsules, binders and packaging methods; see, e.g., U.S. Pat. Nos. 6,922,276 and 7,411,719;
[0012] (c) microcell structures, wall materials, and methods of forming microcells; see, e.g., U.S. Pat. Nos. 7,072,095 and 9,279,906;
[0013] (d) Methods for filling and sealing microlocations; see, e.g., U.S. Patent Nos. 7,144,942; 7,005,468; and 7,715,088; U.S. Patent Application Publication Nos. 2004-0120024; 2004-0219306; 2022-0244612 and 2022-0251364;
[0014] (e) Films and subassemblies containing electro-optical materials; see, e.g., U.S. Pat. Nos. 6,982,178 and 7,839,564;
[0015] (f) Backplanes, adhesive layers and other auxiliary layers and methods for displays; see, e.g., U.S. Pat. Nos. 7,116,318 and 7,535,624;
[0016] (g) color formation and color adjustment; see, e.g., U.S. Pat. Nos. 7,075,502 and 7,839,564;
[0017] (h) Methods for driving displays; see, e.g., U.S. Pat. Nos. 7,012,600 and 7,453,445;
[0018] (i) Display applications; see, e.g., U.S. Pat. Nos. 7,312,784 and 8,009,348; and
[0019] (j) Non-electrophoretic displays; as described in U.S. Patent No. 6,241,921 and U.S. Patent Application Publication No. 2015 / 0277160; and applications of packaging and microcell technology other than displays; see, for example, U.S. Patent No. 7,615,325; and U.S. Patent Application Publications Nos. 2015 / 0005720 and 2016 / 0012710.
[0020] The contents of all of the above references are incorporated herein by reference in their entirety.
[0021] Structures with multiple sealed microcells are commercially used in electro-optical devices, wherein the sealed microcells contain a dispersion of charged pigment particles in a non-polar fluid. Microcells are also referred to as microcavities or microcups in the literature. A general method for making a sealed microcell structure for an electro-optical device comprises (a) making a polymer sheet with multiple microcavities by micro-imprinting, wherein each microcavity has an opening, (b) filling the microcavities with an electrophoretic medium, which is a dispersion of charged pigment particles contained in a non-polar fluid, and (c) sealing the microcavities with a sealing composition to form a sealing layer. The sealed microcavities containing the electrophoretic medium form an electro-optical material layer of the device. The electro-optical material layer is disposed between the front electrode and the rear electrode. Applying an electric field across the electrophoretic medium through these electrodes causes the pigment particles to migrate through the electrophoretic medium, producing an image. The sealing layer plays an important role in the function and performance of the device.
[0022] First, because the sealing layer contacts the electrophoretic medium and seals it within the microcavity, (1) it must be virtually insoluble in the nonpolar fluid of the electrophoretic medium, and (2) it must be a good barrier to the nonpolar fluid so that the nonpolar fluid does not diffuse out of the microcell during the life of the device. Poor barrier properties of the sealing layer to the nonpolar fluid result in reduced fluid from the electrophoretic medium and cause the sealing layer to sag.
[0023] Secondly, in certain applications, where the electrophoretic device may be exposed to harsh conditions such as exposure to or even insertion into water, the sealing layer needs to be waterproof. In other words, the sealing layer must be resilient in water and must protect the electrophoretic medium under such conditions.
[0024] The technical problem of providing a sealing composition that forms a sealing layer with all these characteristics is difficult, because different targets may require different formulation strategies. For example, the barrier properties to non-polar fluids generally require a more hydrophilic component of the sealing layer, and this component is more sensitive to water. Therefore, there is a demand for a sealing composition that forms an optimized sealing layer for improved barrier to non-polar fluids and improved water resistance. The inventors of the present invention have found that the sealing layer formed by the aqueous sealing composition comprising a combination of polyurethane and polyvinyl alcohol has good water resistance and good barrier properties to non-polar fluids and good electro-optical properties, and the polyvinyl alcohol contains acetoacetate functional groups in its molecular structure. SUMMARY OF THE INVENTION
[0026] In one aspect, the present invention relates to a sealing layer comprising (i) 40 to 95% by weight of polyvinyl alcohol, which contains acetoacetate functional groups in its molecular structure, based on the weight of the sealing layer excluding solvents; and (ii) 5 to 60% by weight of polyurethane, based on the weight of the sealing layer excluding solvents. The peak melting temperature of the polyurethane is 115°C and higher, and the crystallinity index is 8% and higher. The polyurethane of the sealing layer may be an ester polyurethane, an ether polyurethane, or a polycarbonate polyurethane. The polyurethane may have a number average molecular weight of 1000 to 2000000 Daltons. The polyurethane of the sealing layer may be cross-linked. The polyurethane cross-linking agent may be a polyisocyanate, a multifunctional polycarbodiimide, a multifunctional aziridine, a silane coupling agent, a boron / titanium / zirconium-based cross-linking agent, or melamine formaldehyde. The polyvinyl alcohol of the sealing layer may be cross-linked. The polyvinyl alcohol of the sealing layer may have a number average molecular weight of 1000 to 1000000 Daltons. The degree of hydrolysis of the polyvinyl alcohol may be 90% to 99%. The polyvinyl alcohol may be cross-linked. The cross-linked polyvinyl alcohol can be formed by the reaction of polyvinyl alcohol and a cross-linking agent, the cross-linking agent being selected from dialdehydes and organic zirconates. The cross-linking agent of the polyvinyl alcohol can be selected from glyoxal, ZrO(OH)Cl*nH2O and (NH4)2ZrO(CO3)2. The polyurethane and the polyvinyl alcohol of the sealing layer can both be cross-linked. The polyvinyl alcohol of the sealing layer can be non-cross-linked. The sealing layer can include a surfactant. The surfactant of the sealing layer can be an acetylenic diol or an organosiloxane surface tension reducer.
[0027] The sealing layer can be formed by an aqueous sealing composition. The aqueous sealing composition can include: (i) 40 to 95% by weight of polyvinyl alcohol, which contains acetoacetate functional groups in its molecular structure, based on the weight of the aqueous sealing composition excluding the solvent; and (ii) 5 to 60% by weight of polyurethane, based on the weight of the aqueous sealing composition excluding the solvent, and (iii) an aqueous carrier. The polyurethane in the aqueous sealing composition can be an ester polyurethane, an ether polyurethane, or a carbonate polyurethane. The polyurethane in the aqueous sealing composition can have a peak melting temperature of 115°C and above and a crystallinity index of 8% and above. The polyurethane can have a number average molecular weight of 1000 to 2000000 Daltons. The aqueous sealing composition can further include a polyurethane crosslinker. The polyurethane crosslinker can be a polyisocyanate, a multifunctional polycarbodiimide, a multifunctional aziridine, a silane coupling agent, a boron / titanium / zirconium-based crosslinker, or melamine formaldehyde. The aqueous sealing composition can be free of a polyvinyl alcohol crosslinker. The aqueous sealing composition can include a polyvinyl alcohol crosslinker. The shelf life of the aqueous sealing composition comprising a polyvinyl alcohol crosslinker may be greater than 1 day, greater than 3 days, greater than 5 days, or greater than 7 days. The number average molecular weight of the polyvinyl alcohol in the aqueous sealing composition may be 1000 to 1000000 Daltons. The degree of hydrolysis of the polyvinyl alcohol may be 90% to 99%. The aqueous sealing composition may comprise both a polyurethane crosslinker and a polyvinyl alcohol crosslinker. The sealing layer may comprise a surfactant. The surfactant of the sealing layer may be an acetylenic diol or an organosiloxane surface tension reducer. The aqueous sealing composition may comprise a polymeric rheology modifier. The polymeric rheology modifier may be a hydrophobically modified alkali swellable acrylic emulsion.
[0028] The sealing layer can be used to seal the microcells of the electrophoretic display. The electrophoretic display may include a first light-transmitting electrode layer, an electro-optical material layer and a second electrode layer in sequence. The electro-optical material layer includes a sealing layer and a microcell layer. The microcell layer includes a plurality of microcells, each of which includes a bottom, a wall and an opening, and contains an electrophoretic medium. The electrophoretic medium contains at least one type of charged pigment particles dispersed in a non-polar fluid. The electrophoretic fluid may include two or more types of charged pigment particles. The electrophoretic medium may contain four types of charged pigment particles, wherein the colors of the four or more pigment particles are selected from white, magenta, yellow, cyan, blue, red, green and black. The sealing layer spans the openings of the plurality of microcells. The sealing layer may be disposed between the microcell layer and the second electrode layer. The sealing layer may be disposed between the microcell layer and the first light-transmitting electrode layer. The sealing layer comprises: (i) 40 to 95 weight % of polyvinyl alcohol, which contains acetoacetate functional groups in its molecular structure, based on the weight of the sealing layer excluding the solvent; and (ii) 5 to 60 weight % of polyurethane, based on the weight of the sealing layer excluding the solvent. The electrophoretic display may further include a piezoelectric material layer, wherein stress on the piezoelectric material layer causes an optical change in the electro-optical material layer. The piezoelectric material layer may be disposed between (a) the electro-optical material layer and the first light-transmitting electrode layer, or (b) between the electro-optical material layer and the second electrode layer.
[0029] The sealing layer can also be used to seal the micro-units of the front plane laminate. The front plane laminate may include a first light-transmitting electrode layer, an electro-optical material layer, an adhesive layer and a release sheet. The electro-optical material layer is located between the first light-transmitting electrode layer and the second electrode layer. The electro-optical material layer includes a plurality of micro-units and a sealing layer.
[0030] The sealing layer can also be used to seal the micro-units of the front plane laminate. The front plane laminate may include a first light-transmitting electrode layer, an electro-optical material layer, an adhesive layer and a release sheet. The electro-optical material layer is arranged between the first light-transmitting electrode layer and the second electrode layer. The electro-optical material layer includes a plurality of micro-units and a sealing layer.
[0031] The sealing layer can also be used to seal the microcells of the front plane laminate. The front plane laminate may include a first light-transmitting electrode layer, an electro-optical material layer, an adhesive layer and a release sheet. The electro-optical material layer is arranged between the first light-transmitting electrode layer and the second electrode layer. The electro-optical material layer includes a plurality of microcells and a sealing layer. The sealing layer can be formed by an aqueous sealing composition. Each microcell in the plurality of microcells includes a bottom, a wall and an opening, and contains an electrophoretic medium, wherein the electrophoretic medium contains at least one type of charged pigment particles dispersed in a non-polar fluid. The sealing layer spans the openings of the plurality of microcells. The front plane laminate may further include a piezoelectric material layer, wherein the stress on the piezoelectric material layer causes an optical change in the electro-optical material layer. The piezoelectric material layer may be arranged between (a) the electro-optical material layer and the first light-transmitting electrode layer, (b) between the electro-optical material layer and the adhesive layer, or (c) side by side near the electro-optical material layer.
[0032] The sealing layer can also be used to seal the microcells of the dual release sheet. The dual release sheet may include a first release sheet, a first adhesive layer, an electro-optical material layer, a second adhesive layer and a second release sheet. The electro-optical material layer may include a plurality of microcells and a sealing layer. The sealing layer may be formed by an aqueous sealing composition. Each of the plurality of microcells includes a bottom, a wall and an opening, and contains an electrophoretic medium, wherein the electrophoretic medium comprises at least one type of charged pigment particles dispersed in a non-polar fluid. The sealing layer spans the openings of the plurality of microcells. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The diagram illustrates the structure of a plurality of microcells before they are filled and sealed.
[0035] Figure 2 An example of an electro-optical device including a microcell structure is illustrated.
[0036] Figure 3 An example of a front plane laminate assembly that can be used to form an electro-optical device including a microcell structure is illustrated.
[0037] Figure 4 An example of a dual release sheet that can be used to form an electro-optical device including a microcell structure is illustrated.
[0038] Figure 5 A method of manufacturing a micro unit using a roll-to-roll method is shown.
[0039] Fig. 6A and 6B DETAILED DESCRIPTION Microcells are fabricated using photolithographic exposure through a photomask coated with a conductor film of a thermosetting precursor.
[0040] Figure 6C and 6D An alternative embodiment is described in detail in which photolithography is used for fabrication. Figure 6C and6D In the embodiment, a combination of top and bottom exposure is used, so that exposure through the top photomask cures the walls in one lateral direction, and bottom exposure through the opaque base conductor film cures the walls in the other lateral direction.
[0041] Figures 7A-7D Diagram illustrating the steps of filling and sealing a microcell array.
[0042] Figure 8-13 The diagram illustrates a side view of an electro-optical display of the present invention, the display including a layer of piezoelectric material.
[0043] Fig.14A and 14B The diagram illustrates the structure of the electro-optical device used to evaluate the aqueous sealing composition examples and the corresponding sealing layers.
[0044] Fig.15A and 15B Microscope images showing the evaluation of barrier properties of the microlocations. DETAILED DESCRIPTION OF THE INVENTION
[0046] The term "solvent exclusive" in reference to the weight of the sealant layer of the present invention means that the weight of the sealant layer is referenced excluding water and other solvents that may be present in the sealant layer.
[0047] As used herein, the term "molecular weight" or "MW" refers to number average molecular weight, unless otherwise indicated. Number average molecular weight can be measured by gel permeation chromatography.
[0048] The terms "crosslinking agent" and "crosslinker" are synonymous and refer to an agent that reacts with a crosslinkable polymer to form a crosslinked polymer.
[0049] The term "pot life" of a composition is the amount of time that the composition remains a processable liquid at a particular temperature.
[0050] The degree of hydrolysis of homopolymers and copolymers of polyvinyl alcohol is usually reported by the manufacturer of such polymers and represents the ratio of vinyl alcohol units (moles) to the total vinyl units in the polymer. Other units may include vinyl acetate or other units.
[0051] "Waterproof seal" refers to the integrity of the seal of an electro-optical display after the device has been submerged in water at a specific pH and temperature for a specific period of time.
[0052] As used herein, the term "light-transmissive" is used to refer to a layer so designated that transmits sufficient light to enable an observer viewing through the layer to observe a change in the display state of the electrophoretic medium, which would normally be viewed through the light-transmissive electrode layer and the adjacent substrate (if present); in the case of an electrophoretic medium that exhibits changes in reflectivity at non-visible wavelengths, the term "light-transmissive" should of course be interpreted as referring to transmission of the relevant non-visible wavelengths.
[0053] The term "contrast ratio" (CR) for electro-optical displays is defined as the ratio of the brightness of the brightest color (white) to the brightness of the darkest color (black) the display is capable of producing. Generally, a high contrast ratio or CR is a desirable condition for a display.
[0054] Piezoelectricity is the electrical charge that a solid material accumulates in response to an applied mechanical stress. Suitable piezoelectric materials may include polyvinylidene fluoride (PVDF), quartz (SiO2), Berlinite (AlPO4), gallium orthophosphate (GaPO4), tourmaline, barium titanate (BaTiO3), lead zirconate titanate (PZT), zinc oxide (ZnO), aluminum nitride (AlN), lithium tantalite, lanthanum gallium silicate, potassium sodium tartrate, and any other known piezoelectric material. Piezoelectricity can be used to drive the pigments of the electrophoretic material of an electro-optical display to generate an electrical charge that powers the electro-optical display. An electro-optical display can operate without a power source, powered entirely by the electrical charge generated by the piezoelectric material. For example, in the case of an electro-optical display having an electrophoretic material, a voltage can be generated by bending the piezoelectric material or introducing stress into the piezoelectric material, which voltage can be used to move the color pigments of the electrophoretic material of the electro-optical display. Electro-optic displays including electrophoretic media and piezoelectric materials have been previously disclosed, for example, in US Pat. Nos. 7,002,728 and 7,679,814.
[0055] A. Structure of Microcell
[0056] Figure 1 The diagram illustrates the structure of a plurality of microcells 100 before they are filled and sealed. Each microcell includes a bottom 101 , a wall 102 , and an opening 103 .
[0057] B. Structure of an electro-optical device including a microcell structure
[0058] Figure 2The diagram illustrates an example of an electro-optical device 200 including a plurality of microcells and a sealing layer according to the present invention. This example of the electro-optical device 200 includes a first light-transmitting electrode layer 210, a microcell layer 220, a sealing layer 230, an adhesive layer 240, and a second electrode layer 250. The microcell layer 220 includes a plurality of microcells defined by a bottom 101 and a wall 102. Each of the plurality of microcells has an opening 103. Each of the plurality of microcells contains an electrophoretic medium 225, which contains charged particles in a non-polar fluid. The microcells are sealed with a sealing layer 230, which spans the openings 103 of the plurality of microcells. The second electrode layer 250 is connected to the sealing layer 230 with an adhesive layer 240. The electro-optical material layer 260 of the electro-optical device 200 includes the microcell layer 220 and the sealing layer 230. An electric field source (at Figure 2 The first light-transmitting electrode layer 210 and the second electrode layer 250 may be connected. Application of an electric field across the electro-optic material layer causes the charged particles to migrate through the electrophoretic medium, producing an image that can be viewed by an observer viewing from the viewing side 205 of the electro-optic device 200. The optional primer layer (not shown in FIG. 2 ) may be connected to the first light-transmitting electrode layer 210 and the second electrode layer 250. Application of an electric field across the electro-optic material layer causes the charged particles to migrate through the electrophoretic medium, producing an image that can be viewed by an observer viewing from the viewing side 205 of the electro-optic device 200. Figure 2 The sealing layer is waterproof and contains 40% to 95% by weight of polyvinyl alcohol, which contains acetoacetate functional groups in its molecular structure, based on the weight of the sealing layer excluding the solvent; and 5% to 60% by weight of polyurethane, based on the weight of the sealing layer excluding the solvent.
[0059] Figure 2 The illustrated example of an electro-optical device may be provided by Figure 3 The front plane laminate 300 shown in FIG. The front plane laminate 300 includes a first light-transmitting electrode layer 210, a microcell layer 220 having a plurality of microcells, a sealing layer 230, an adhesive layer 240, and a release sheet 360. Each of the plurality of microcells contains an electrophoretic medium 225, and the electrophoretic medium 225 contains charged particles in a non-polar fluid. The microcells are sealed with a sealing layer 230, and the sealing layer 230 spans the openings of the plurality of microcells. The release sheet 360 is connected to the sealing layer 230 with an adhesive layer 240. The electro-optical material layer 260 includes the microcell layer 220 and the sealing layer 230. Removal of the release sheet 360 exposes the surface of the adhesive layer 240, and the adhesive layer 240 can be connected to the second electrode layer to form an electro-optical device. The optional bottom layer (in Figure 3 (not shown) may be disposed between the first light-transmitting electrode layer 210 and the micro unit layer 220.
[0060] Figure 2 The illustrated example of an electro-optical device may also be provided by Figure 44. The double release sheet 400 shown in FIG. 4 is composed of a first release sheet 480, a first adhesive layer 470, a microcell layer 220, a sealing layer 230, a second adhesive layer 240, and a second release sheet 360. Each of the plurality of microcells contains an electrophoretic medium 225, which contains charged particles in a non-polar fluid. The microcell is sealed with a sealing layer 230, which spans the openings of the plurality of microcells. The electro-optical material layer 260 includes a microcell layer 220 and a sealing layer 230. The first release sheet 480 is connected to the microcell layer 220 with a first adhesive layer 470. The second release sheet 360 is connected to the sealing layer 230 with a second adhesive layer 240. Removal of the first release sheet 480 exposes the surface of the first adhesive layer 470, which can be connected to the first light-transmitting electrode layer. Removal of the second release sheet 360 exposes the surface of the second adhesive layer 240, which can be connected to the second electrode layer to form an electro-optical device. Optional bottom layer (in Figure 4 (not shown) may be disposed between the first adhesive layer 470 and the micro unit layer 220. Figure 3 The sealing layer of the front plane laminate 300 and Figure 4 The sealing layers of the dual release sheets 400 in the invention are waterproof. They contain 40% to 95% by weight of polyvinyl alcohol containing acetoacetate functional groups in its molecular structure, based on the weight of the sealing layer excluding solvents, and 5% to 60% by weight of polyurethane, based on the weight of the sealing layer excluding solvents.
[0061] C. Formation of micro-unit structure
[0062] Techniques for constructing microcells. Microcells can be formed in a batch process or in a continuous roll-to-roll process, as disclosed in U.S. Pat. No. 6,933,098. The latter provides a continuous, low-cost, high-throughput manufacturing technology for making compartments for use in a variety of applications including beneficial agent delivery and electrophoretic displays. Figure 5 As illustrated, micro-unit arrays suitable for use in the present invention can be produced using micro-imprinting. The male mold 500 can be placed above the web 504 or below the web 504 (not shown); however, alternative arrangements are possible. For example, see U.S. Pat. No. 7,715,088, which is incorporated herein by reference in its entirety. A conductive substrate can be constructed by forming a conductor film 501 on a polymer substrate, which becomes the backing layer of the device. A composition 502 containing a thermoplastic, a thermosetting substance, or a precursor thereof is then coated on the conductor film. The thermoplastic or thermosetting precursor layer is embossed by a male mold in the form of a roller, plate, or belt at a temperature above the glass transition temperature of the thermoplastic or thermosetting precursor layer.
[0063] The thermoplastic or thermosetting precursors used to prepare the micro-units can be multifunctional acrylates or methacrylates, vinyl ethers, epoxides and their oligomers or polymers, etc. The combination of multifunctional epoxides and multifunctional acrylates is also very useful for achieving the desired physical and mechanical properties. Crosslinkable oligomers such as urethane acrylates or polyester acrylates that impart flexibility can be added to improve the flexural resistance of the imprinted micro-units. The composition can contain polymers, oligomers, monomers and additives or only oligomers, monomers and additives. The glass transition temperature (or T g ) is usually in the range of about -70°C to about 150°C, or about -20°C to about 50°C. Micro-embossing methods are generally carried out at temperatures above T g A heated male mold or heated housing substrate against which the mold is pressed can be used to control the micro-embossing temperature and pressure.
[0064] like Figure 5 As shown, demoulding during or after the precursor layer hardens to reveal the array of microunits 503. The hardening of the precursor layer can be completed by cooling, solvent evaporation, radiation crosslinking, heat or moisture. If the curing of the thermosetting precursor is completed by ultraviolet radiation, the ultraviolet rays can be radiated from the bottom or top of the web to the transparent conductor film, as shown in the two figures. Alternatively, a UV lamp can be placed in the mold. In this case, the mold must be transparent so that the ultraviolet light is radiated to the thermosetting precursor layer through the pre-patterned positive mold. The positive mold can be prepared by any suitable method, such as a diamond turning method or a photoresist method, and then etching or electroplating. The master template for the positive mold can be manufactured by any suitable method, such as electroplating. Using electroplating, a thin layer (generally 200 μm) of a seed metal such as chrome inconel is used to form a positive mold. ) sputtering glass substrate. Then the mold is coated with a photoresist layer and exposed to ultraviolet light. A mask is placed between the ultraviolet light and the photoresist layer. The exposed areas of the photoresist become hardened. Then it is removed by washing the unexposed areas with a suitable solvent. The remaining hardened photoresist is dried and sputtered again with a thin layer of seed metal. Then the master is ready for electroforming. The general material for electroforming is nickel cobalt. Alternatively, the master can be made of nickel by electroforming or chemical nickel deposition. The mold base is generally about 50 to 400 microns. The master can also be manufactured using other microengineering techniques, including electron beam writing, dry etching, chemical etching, laser writing or laser interference, as described in "Replication techniques for micro-optics", SPIE Proc. Vol. 3099, pp. 76-82 (1997). Alternatively, the mold can be manufactured using plastic, ceramic or metal by photomechanical processing.
[0065] Before applying the UV-curable resin composition, the mold can be treated with a release agent to help the demoulding process. The UV-curable resin can be degassed before distribution and can optionally contain a solvent. The solvent (if present) evaporates easily. The UV-curable resin is distributed on the male mold by any suitable means, such as coating, dipping, pouring, etc. The distributor can be mobile or fixed. The conductor film is covered with the UV-curable resin. If necessary, pressure can be applied to ensure that the appropriate combination between the resin and the plastic and the thickness of the bottom of the micro-unit are controlled. Laminating rollers, vacuum molding, pressure devices or any other similar means can be used to apply pressure. If the male mold is metallic and opaque, the plastic substrate is generally transparent to the actinic radiation used to cure the resin. On the contrary, the male mold can be transparent, and the plastic substrate can be opaque to actinic radiation. In order to realize that the molded features are well transferred to the transfer sheet, the conductor film needs to have good adhesion to the UV-curable resin, and the UV-curable resin should have good release properties for the mold surface.
[0066] The microcell array used in the present invention generally includes a preformed conductor film, such as indium tin oxide (ITO) conductor lines; however, other conductive materials, such as silver or aluminum, may be used. The conductive layer may be supported by or integrated into a substrate such as polyethylene terephthalate, polyethylene naphthalate, polyaramide, polyimide, polycycloolefin, polysulfone, epoxy resin, and composites thereof. The conductor film may be coated with a radiation-curable polymer precursor layer. The film and precursor layer are then imagewise exposed to radiation to form a microcell wall structure. After exposure, the precursor material is removed from the unexposed area, leaving a cured microcell wall bonded to the conductor film / support web. Imagewise exposure may be accomplished by ultraviolet light or other forms of radiation through a photomask to produce an image or predetermined pattern of exposure of the radiation-curable material coated on the conductor film. Although generally not required, the mask may be positioned and aligned relative to the conductor film, i.e., the ITO lines, so that the transparent mask portion is aligned with the space between the ITO lines and the opaque mask portion is aligned with the ITO material (intended for the bottom area of the microcell).
[0067] Photolithography. Microcells can also be made using photolithography. Photolithography methods for making microcell arrays are Fig. 6A and 6B The diagram in the figure shows the following. Fig. 6A and 6BAs shown, microcell array 600 can be prepared by exposing radiation-curable material 601a coated onto conductor film 602 by known methods to ultraviolet light (or alternatively to other forms of radiation, electron beams, etc.) through mask 606 to form walls 102 corresponding to the image projected through mask 606. Base conductor film 602 is preferably mounted on a supporting substrate base web (603), which can include a plastic material.
[0068] exist Fig. 6A In the photomask 606 in FIG. 1 , dark squares 604 represent opaque areas of the mask 606, and the spaces between the dark squares represent transparent areas 605 of the mask 606. The ultraviolet radiation reaches the radiation-curable material 601a through the transparent areas 605. The exposure is preferably performed directly on the radiation-curable material 601a, i.e., the ultraviolet light does not pass through the substrate 603 or the base conductor film 602 (top exposure). For this reason, neither the substrate 603 nor the conductor film 602 need to be transparent to the ultraviolet light or other radiation wavelengths used.
[0069] like Figure 6B As shown, the exposed areas such as wall 102 become hardened. The unexposed areas (protected by the opaque areas 604 of the mask 606) are then removed by a suitable solvent or developer to form microcells 607. The solvent or developer is selected from those commonly used to dissolve radiation-curable materials or reduce the viscosity of radiation-curable materials, such as methyl ethyl ketone (MEK), toluene, acetone, isopropyl alcohol, etc. The preparation of microcells can be similarly accomplished by placing a photomask under the conductor film / substrate support web. In this case, the UV light is radiated through the photomask from the bottom, and the substrate needs to be transparent to the radiation.
[0070] Imagewise exposure. Another alternative method for preparing the microunit array of the present invention by imagewise exposure is Figure 6C and 6D When opaque conductor lines are used, the conductor lines can be used as a photomask for exposure from the bottom. Additional exposure from the top through a second photomask with opaque lines perpendicular to the conductor lines forms durable microcell walls. Figure 6CThe diagram illustrates the use of the top and bottom exposure principles to manufacture the microcell array 610 of the present invention. The base conductor film 612 is opaque and line patterned. The radiation-curable material 611a coated on the base conductor film 612 and the substrate 603 is exposed from the bottom through the conductor line pattern 612 used as a first photomask. A second exposure is performed from the "top" side through a second photomask 616 having a line pattern perpendicular to the conductor lines 612. The spaces 615 between the lines 614 are substantially transparent to ultraviolet light. In this process, the wall material 611a is cured from the bottom up in a lateral orientation and from the top down in a vertical direction, connecting to form the walls 102 of the overall microcell 607. As shown in FIG. Fig.6D As shown, the unexposed areas are then removed by a solvent or developer as described above to reveal the microelements 607.
[0071] The microunits may be composed of thermoplastic elastomers that have good compatibility with the microunits and do not interact with the medium. Examples of useful thermoplastic elastomers include ABA and (AB)n type diblock, triblock and multiblock copolymers, wherein A is styrene, α-methylstyrene, ethylene, propylene or norbornene; B is butadiene, isoprene, ethylene, propylene, butylene, dimethylsiloxane or propylene sulfide; wherein A and B cannot be the same. The number n ≥ 1, preferably 1-10. Particularly useful are diblock or triblock copolymers of styrene or oxymethylstyrene, such as SB (poly(styrene-b-butadiene)), SBS (poly(styrene-b-butadiene-b-styrene)), SIS (poly(styrene-b-isoprene-b-styrene)), SEBS (poly(styrene-b-ethylene / butylene-b-styrene)), poly(styrene-b-dimethylsiloxane-b-styrene), poly(α-methylstyrene-b-isoprene), poly(α-olefin-b-isoprene-b-α-methylstyrene), poly(α-methylstyrene-b-propylene sulfide-b-α-methylstyrene), poly(α-methylstyrene-b-dimethylsiloxane-b-α-methylstyrene). Commercially available styrene block copolymers, such as the Kraton D and G series (from Kraton Polymer, Houston, Tex.), are particularly useful. Crystalline rubbers, such as poly(ethylene-co-propylene-co-5-methylene-2-norbornene) or EPDM (ethylene-propylene-diene terpolymer) rubbers, such as Vistalon 6505 (from Exxon Mobil, Houston, Tex.), and graft copolymers thereof have also been found to be very useful.
[0072] The thermoplastic elastomer can be dissolved in a solvent or solvent mixture that is immiscible with the carrier in the microcell and exhibits a specific gravity less than that of the carrier. Low surface tension solvents are preferably used in the outer coating composition due to their better wetting properties than the microcell walls and the fluid. Solvents or solvent mixtures having a surface tension of less than 35 dynes / cm or less than 30 dynes / cm are preferred. Suitable solvents include alkanes (preferably C 6-12 Alkanes such as heptane, octane or Isopar solvents from Exxon Chemical Company, nonane, decane and their isomers), cycloalkanes (preferably C 6-12 Cycloalkanes such as cyclohexane and decalin), alkylbenzenes (preferably mono- or di-C 1-6 Alkylbenzenes, such as toluene, xylene, etc.), alkyl esters (preferably C 2-5 Alkyl esters such as ethyl acetate, isobutyl acetate, etc.) and C 3-5 Alkyl alcohols (such as isopropanol and the like and their isomers), alkylbenzenes and mixtures of alkanes are particularly useful.
[0073] In addition to polymer additives, the polymer mixture may also include a wetting agent (surfactant). Wetting agents (such as FC surfactants from 3M Company, Zonyl fluorosurfactants from DuPont, fluoroacrylates, fluoromethacrylates, fluorinated long chain alcohols, perfluorinated long chain carboxylic acids and their derivatives, and Silwet organosiloxane surfactants from OSi, Greenwich, Conn) may also be included in the composition to improve the adhesion of the sealant to the microcells and provide a more flexible coating method. Other ingredients, including crosslinking agents (e.g., bisazides such as 4,4'-diazidediphenylmethane and 2,6-bis-(4'-azidobenzylidene)-4-methylcyclohexanone), vulcanizing agents (e.g., 2-benzothiazolyl disulfide and tetramethylthiuram disulfide), multifunctional monomers or oligomers (e.g., hexanediol, diacrylates, trimethylolpropane, triacrylates, divinylbenzene, diallylphthalene), thermal initiators (e.g., dilauroyl peroxide, benzoyl peroxide), and photoinitiators (e.g., isopropylthioxanthone (ITX), Irgacure 651 and Irgacure 369 from Ciba-Geigy) are also very useful for enhancing the physical-mechanical properties of the sealing layer by crosslinking or polymerization during or after the overcoating process.
[0074] The microcell array 700 can be prepared by any of the methods described above. Figures 7A-7DAs shown in the cross-section in FIG. 1 , microcell walls 102 extend upward from backing layer 101 (the bottom of the microcell) and conductive layer 210 to form an open microcell, and the conductive layer 210 can serve as the first light-transmitting electrode layer of the electro-optical device. In one embodiment, conductive layer 210 is formed on or at backing layer 101. Although Figures 7A-7D Conductive layer 210 is shown to be continuous and extend over backing layer 101 , but conductive layer 210 may also be continuous and extend under or within backing layer 101 , or it may also be interrupted by microcell walls 102 .
[0075] Next, the microcells are filled with an electrophoretic medium 225, which contains charged particles in a non-polar fluid to form a plurality of filled microcells. Various techniques can be used to fill the microcells. In some embodiments, a doctor blade can be used to fill the microcells to the depth of the microcell walls 102. In other embodiments, inkjet microinjection can be used to fill the microcells. In other embodiments, a microneedle array can be used to fill the electrophoretic medium 225 into the microcell array.
[0076] like Figure 7C As shown, after filling, the microcell is sealed by applying an aqueous sealing composition to form a sealed microcell 780 including a sealing layer 230. In some embodiments, the sealing process may include exposure to heat, dry hot air, or ultraviolet radiation. The sealing layer must have good barrier properties to the non-polar fluid of the electrophoretic medium 225.
[0077] In an alternative embodiment, each individual microcell can be filled with the desired mixture by using an iterative photolithography process. The method generally includes coating an empty microcell array with a positive working photoresist layer, selectively opening a certain number of microcells by imagewise exposure of the positive photoresist, then developing the photoresist, filling the opened microcells with the desired mixture, and sealing the filled microcells by a sealing process. These steps can be repeated to produce sealed microcells filled with other mixtures. The process can form a large sheet of microcells having a desired mixture ratio or concentration ratio.
[0078] The sealing of the filled microcells can be accomplished in a variety of ways. One method includes mixing an aqueous sealing composition with an electrophoretic medium composition. The aqueous sealing composition may be immiscible with the electrophoretic composition, preferably having a specific gravity lower than that of the electrophoretic medium composition. The two compositions—the aqueous sealing composition and the electrophoretic medium composition—are fully mixed and immediately applied to a plurality of microcells using a precision coating mechanical device such as a Mayer rod, gravure printing, a scraper, a slot coating or a slit coating. Excess fluid is scraped off by a scraper or similar device. A small amount of weak solvent or solvent mixture, such as isopropanol, methanol or its aqueous solution, can be used to clean the residual fluid on the top surface of the microcell partition wall. The aqueous sealing composition is then separated from the electrophoretic medium composition and floats on the top of the electrophoretic medium liquid composition. Alternatively, after the mixture of the electrophoretic medium composition and the aqueous sealing composition is filled into the microcell, a substrate can be laminated on the top to control the mixture metering of the composition and promote the phase separation of the aqueous sealing composition and the electrophoretic medium composition to form a uniform sealing layer. The substrate used can be a functional substrate in the final structure, or can be a sacrificial substrate, such as a release substrate, which can be removed later. The sealing layer is then formed by hardening the aqueous sealing composition in situ (i.e. when in contact with the electrophoretic medium composition). The hardening of the aqueous sealing composition can be accomplished by ultraviolet rays or other forms of radiation, such as visible light, IR or electron beams. Alternatively, if a heat-curable or moisture-curable aqueous sealing composition is used, heat or moisture can also be used to harden the aqueous sealing composition.
[0079] In another method, the electrophoretic medium composition can be first filled into the microcell, and the aqueous sealing composition is then coated on the filled microcell. The coating can be completed by conventional coating and printing methods, such as blanket coating, inkjet printing or other printing methods. In this method, the sealing layer is formed in situ by hardening the aqueous sealing composition by solvent evaporation, radiation, heat, moisture or interfacial reaction. UV curing after interfacial polymerization is beneficial to the sealing process. By forming a thin barrier layer at the interface through interfacial polymerization, the mixing between the electrophoretic medium composition and the sealing outer coating is significantly suppressed. Then the sealing is completed by a post-curing step, such as by ultraviolet radiation. The degree of mixing can be further reduced by using an aqueous sealing composition with a specific gravity lower than that of the electrophoretic medium composition. Volatile organic solvents can be used to adjust the viscosity and thickness of the sealing outer coating. The rheology of the aqueous sealing composition can be adjusted to obtain optimal sealability and coatability. When a volatile solvent is used in the outer coating, it is preferably immiscible with the solvent in the electrophoretic medium composition.
[0080] After filling and sealing the microcells, the sealed array can be laminated with a second electrode layer 250 comprising a plurality of electrodes. The second electrode layer 250 can be attached to the sealing layer 230 to form an electro-optical device 790, such as Fig.7D As shown. An adhesive can be used to attach the second electrode layer 250 to the sealing layer 230 (the adhesive layer is not Fig.7D ). The adhesive can be conductive. The adhesive of the adhesive layer can be a pressure sensitive adhesive, a hot melt adhesive, or an adhesive that can be cured by heat, moisture, or radiation. If the top conductive layer is transparent to radiation, the laminating adhesive can be cured by radiation, such as ultraviolet light, through the top conductive layer. In other embodiments, multiple electrodes can be directly bonded to the array of sealed microcells.
[0081] In general, the microcells can be of any shape, and their size and shape can vary. In one system, the microcells can have a consistent size and shape. However, microcells with mixed shapes and sizes are possible. The openings of the microcells can be circular, square, rectangular, hexagonal, or any other shape. The size of the separation area between the openings can also vary. The size of each individual microcell can be between about 1×10 1 About 1×10 6 μm 2 , about 1×10 2 About 1×10 6 μm 2 , or about 1×10 3 About 1×10 5 μm 2 range.
[0082] The depth of the microcell may range from about 5 μm to about 200 μm or from about 10 μm to about 100 μm. The ratio of the opening area to the total area ranges from about 0.05 to about 0.95, or from about 0.4 to about 0.9.
[0083] Electrophoretic displays typically include an electro-optical material layer and at least two other layers disposed on opposite sides of the electrophoretic material, one of the two layers being an electrode layer. In most such displays, both layers are electrode layers, and one or both of the electrode layers are patterned to define the pixels of the display. For example, one electrode layer may be patterned as an elongated row electrode and the other electrode layer may be patterned as an elongated column electrode extending at right angles to the row electrode, with the pixel being defined by the intersection of the row electrode and the column electrode. Alternatively and more commonly, one electrode layer has the form of a single continuous electrode and the other electrode layer is patterned as a matrix of pixel electrodes, each of which defines a pixel of the display. In another type of electrophoretic display intended for use with a stylus, print head or similar movable electrode separated from the display, only one of the layers adjacent to the electro-optical material layer includes an electrode, and the layer on the opposite side of the electro-optical material layer is generally a protective layer intended to prevent the movable electrode from damaging the electro-optical material layer.
[0084] The manufacture of three-layer electro-optical displays typically involves at least one lamination operation. For example, in several of the above-mentioned MIT and E Ink patents and applications, there is a description of a method for manufacturing an encapsulated electrophoretic display, in which an encapsulated electrophoretic medium containing capsules in a binder is applied to a flexible substrate containing indium tin oxide (ITO) or a similar conductive coating on a plastic film. A backplane is prepared separately, the backplane containing an array of pixel electrodes and an appropriate conductor arrangement to connect the pixel electrodes to a drive circuit. To form the final display, the substrate with the electro-optical material layer is laminated to the backplane using a laminating adhesive.
[0085] The aforementioned U.S. Patent No. 6,982,178 describes a method of assembling a solid electro-optical display that is well suited for large-scale manufacturing. Basically, the patent describes a so-called "front plane laminate" ("FPL") that includes, in order, a light-transmitting electrode layer; a layer of electro-optical material in electrical contact with the light-transmitting electrode layer; an adhesive layer; and a release sheet. Generally, the light-transmitting electrode layer will be carried on a light-transmitting substrate, which is preferably flexible in the sense that the substrate can be manually wrapped around a roller having a diameter of (supposedly) 10 inches (254 mm) without permanent deformation. The substrate will generally be a polymer film and will generally have a thickness ranging from about 1 to about 25 mils (25 to 634 μm), preferably from about 2 to about 10 mils (51 to 254 μm). The light-transmitting electrode layer is conveniently a thin metal or metal oxide layer, such as an aluminum layer or an ITO layer, or may be a conductive polymer. Poly(ethylene terephthalate) (PET) films coated with aluminum or ITO are commercially available, for example, from EI duPont de Nemours & Company, Wilmington DE as "aluminized Mylar" ("Mylar" is a registered trademark), and this commercial material can be used in the front plane laminate with good results. Assembly of an electrophoretic display using such a front plane laminate can be achieved by removing a release sheet from the front plane laminate and contacting the adhesive layer with the backplane under conditions effective to adhere the adhesive layer to the backplane, thereby fixing the adhesive layer, the electro-optical material layer, and the light-transmitting electrode layer to the backplane. This method is well suited for large-scale manufacturing because the front plane laminate can be manufactured on a large scale, generally using roll-to-roll coating techniques, and then cut into sheets of any size required for use with a particular backplane.
[0086] U.S. Patent No. 7,561,324 describes a so-called "double release sheet" which is essentially a simplified version of the front plane laminate of the aforementioned U.S. Patent No. 6,982,178. One form of the double release sheet comprises a layer of electro-optic material sandwiched between two adhesive layers, one or both of which are covered by a release sheet. Another form of the double release sheet comprises a layer of solid electro-optic material sandwiched between two release sheets. Both forms of double release films are intended for use in a process generally similar to that used to assemble an electrophoretic display from the front plane laminate already described, but involving two separate laminations; typically, in a first lamination, the double release sheet is laminated to the front electrode to form a front subassembly, and then in a second lamination, the front subassembly is laminated to the backplane to form the final display, although the order of the two laminations may be reversed if desired.
[0087] U.S. Patent No. 7,839,564 describes a so-called "inverted front plane laminate", which is a variation of the front plane laminate described in the above-mentioned U.S. Patent No. 6,982,178. The inverted front plane laminate may include, in sequence: at least one of a light-transmitting protective layer and a light-transmitting electrode layer; an adhesive layer; an electro-optic material layer; and a release sheet. The inverted front plane laminate is used to form an electro-optical device having a laminated adhesive layer between the electro-optical material layer and the light-transmitting electrode layer; a second, generally thin adhesive layer may or may not be present between the electro-optical material layer and the backplane. Such an electro-optical display may combine good resolution with good low temperature performance.
[0088] The electrophoretic display of the present invention may include a piezoelectric material layer including a piezoelectric material. Such an electrophoretic display can operate without a power supply. This means that the structure of the electrophoretic display is simplified. The piezoelectric material layer may be arranged (a) between the electro-optical material layer and the first light-transmitting electrode layer, (b) between the electro-optical material layer and the second electrode layer, or (c) side by side with the electro-optical material layer.
[0089] Piezoelectricity is the accumulation of electrical charge in a solid material (piezoelectric material) in response to an applied mechanical stress. Examples of piezoelectric materials include polyvinylidene fluoride (PVDF), quartz (SiO2), Berlinite (AlPO4), gallium orthophosphate (GaPO4), tourmaline, barium titanate (BaTiO3), lead zirconate titanate (PZT), zinc oxide (ZnO), aluminum nitride (AlN), lithium tantalate, lanthanum gallium silicate, potassium sodium tartrate, and any other known piezoelectric material. The piezoelectric material layer may further contain an ionic liquid.
[0090] The piezoelectrically generated voltage can drive the pigments of the electrophoretic material layer to change the color or image of the electrophoretic material when viewed from the viewing side of the display. For example, by bending the electro-optic display or introducing stress to the electro-optic display containing the piezoelectric material layer, a voltage can be generated that can be used to move the color pigments of the electrophoretic material.
[0091] Figure 8 An example of an electro-optical display including a piezoelectric material layer and a sealing layer according to the present invention is shown. Figure 8 8 is a cross-sectional view of an electro-optic display 800, which includes a piezoelectric material layer 802 that can drive an electro-optic material layer 260. The electro-optic display includes a first light-transmitting electrode layer 210, an electro-optic material layer 260, a piezoelectric material layer 802, and a second electrode layer 250. The piezoelectric material layer 802 is located between the second electrode layer 250 and the electro-optic material layer 260, and the electro-optic material layer 260 is disposed between the first electrode layer 210 and the piezoelectric material layer 802. The electro-optic material layer 260 may include a plurality of micro units (in Figure 8Each of the plurality of microcells comprises a bottom, a wall and an opening, and contains an electrophoretic medium. Figure 8 The sealing layer may be located adjacent to the piezoelectric material layer 802. The first light-transmitting electrode layer 210 may have the form of a single continuous electrode (also referred to as a conductive layer), and the second electrode layer 250 may include a plurality of pixel electrodes (pixel electrode matrix). The display may be bent by a user to generate a voltage sufficient to operate the display.
[0092] Fig. 9 The cross-sectional view of another example of an electro-optic display 900 is illustrated, and the electro-optic display 900 includes a piezoelectric material layer 802 that can drive an electro-optic material layer 260. The electro-optic material layer includes a first light-transmitting electrode layer 210, a piezoelectric material layer 802, the electro-optic material layer 260, and a second electrode layer 250. The piezoelectric material layer 802 is located between the first light-transmitting electrode layer 250 and the electro-optic material layer 260, and the electro-optic material layer 260 is disposed between the second electrode layer 250 and the piezoelectric material layer 802. The electro-optic material layer 260 may include a plurality of micro-units ( Fig. 9 Each of the plurality of micro-units comprises a bottom, a wall and an opening, and contains an electrophoretic medium. Figure 8 The sealing layer may be located adjacent to the second electrode layer 250. The sealing layer may be located adjacent to the piezoelectric material layer 802. The electro-optical display may further include an adhesive layer ( Fig. 9 (not shown), the adhesive layer is disposed between the electro-optic material layer 260 and the second electrode layer 250. Specifically, the piezoelectric material layer may be in contact with the sealing layer of the electro-optic material layer 260. The first light-transmitting electrode layer 210 may have the form of a single continuous electrode (also referred to as a conductive layer), and the second electrode layer 250 may include a plurality of pixel electrodes (pixel electrode matrix).
[0093] Fig.10 The diagram illustrates a cross-sectional view of an example of an electro-optic display 1000 according to the present invention, which includes (1) a piezoelectric material layer 802 that can drive the electro-optic material layer 260, and (2) a sealing layer according to the present invention. The electro-optic material layer includes a first light-transmitting electrode layer 210, an electro-optic material layer 260, a piezoelectric material layer 802, and a second electrode layer 250. In this embodiment, the piezoelectric material layer 802 is located between the electro-optic material layer and the second electrode layer 250. The piezoelectric material layer 802 overlaps only a first portion of the electrophoretic material layer 260. The second electrode layer 250 overlaps the entire piezoelectric material layer 802 and a second portion of the electro-optic material layer, wherein the second portion of the electro-optic material layer does not overlap with the piezoelectric material layer 802. The first portion of the electro-optic material layer may include a first plurality of microunits ( Fig.10 ), and may have a first resistance, and the second portion of the electro-optical material layer may include a second plurality of microunits ( Fig.10 (not shown) and may have a second resistor. Fig.10 As shown, the first light-transmitting electrode layer 210 is adjacent to the electro-optic material layer 260 , and is located on the other side of the electro-optic material layer 260 relative to the piezoelectric material layer and the second electrode layer 250 .
[0094] Each of the first and second plurality of microcells comprises a bottom, a wall and an opening, and contains an electrophoretic medium. Fig.10 The sealing layer may be located adjacent to the piezoelectric material layer 802 and the second electrode layer 250 (on the side of the electro-optic material layer opposite to the first light-transmitting electrode layer 210).
[0095] In another example, the piezoelectric material layer 802 can be laminated on the semiconductive or high resistance layer 1112, and then the semiconductive or high resistance layer 1112 is laminated on the first light-transmitting electrode layer 210, such as Fig.11 As shown, rather than Figure 8 , 9 As shown in FIG. 10 , the piezoelectric material layer is directly laminated on or overlaps the electro-optic material layer. In this configuration, the electro-optic display 1100 includes a semi-conductive or high-resistance layer 1112. The semi-conductive or high-resistance layer 1112 replaces a portion of the electro-optic material layer 260 on top of the piezoelectric material layer 802, thereby reducing the overall thickness of the display and preventing the charge from being quickly dissipated on the piezoelectric material layer 802, so that the locally generated charge (by the piezoelectric material layer 802) can be effectively and efficiently applied to the electro-optic material layer 260. This results in an improvement in the contrast of the display. As shown in FIG. Fig.11 As shown, the first light-transmitting electrode layer 210 and the second electrode layer 250 sandwich an electro-optic material layer 260, a semi-conductive or high-resistance layer 1112 and a piezoelectric material layer 802. The electro-optic material layer 260 may include a plurality of micro-units ( Fig.11 Each of the plurality of micro-units comprises a bottom, a wall and an opening, and contains an electrophoretic medium. Fig.11 The sealing layer (not shown) spans across the openings of multiple micro-units. Fig.11 The sealing layer (not shown) may be located adjacent to the first electrode layer 210. Fig.11 (not shown) may be located adjacent to the second electrode layer 250.
[0096] In another example, Fig.12 The diagram illustrates a cross-sectional view of an electro-optic display 1200 including a piezoelectric layer and a sealing layer according to the present invention. Fig.11 The display shown is different in that only a portion of the piezoelectric material layer 802 overlaps the first light-transmitting electrode layer 210. In this configuration, the piezoelectric material layer 802 can avoid being located in a neutral plane position, so that a better image can be produced by the piezoelectric material layer 802. In addition, the piezoelectric material layer 802 can be a metallized piezoelectric material layer and can be covered by a metal layer 1213. In some embodiments, the first semiconductive layer 1112 can be located between the metal layer 1213 and the first electrode light-transmitting layer 210. Another semiconductive layer, namely the second semiconductive layer 1210, can be located between the piezoelectric material layer 802 and the second electrode layer 250. It should be understood that all layers presented herein, including the first electrode layer 210 and the second electrode layer 250, can be light-transmitting so that the display can be viewed from any direction or orientation. The electro-optical material layer 260 may include a plurality of microcells ( Fig.12 Each of the plurality of micro-units comprises a bottom, a wall and an opening, and contains an electrophoretic medium. Fig.12 The sealing layer (not shown) spans across the openings of multiple micro-units. Fig.12 The sealing layer (not shown) may be located adjacent to the second electrode layer 250. Fig.12 ) may be located adjacent to the second semiconducting layer 1210.
[0097] Fig.13 FIG. 1 is a cross-sectional view of another example of an electro-optic display 1300. The electro-optic display 1300 according to the present invention includes a piezoelectric material layer and a sealing layer. Fig.13 As shown, the electro-optic material layer 260 may partially extend below the piezoelectric material layer 802 to overlap, ensuring a secure connection with the piezoelectric material layer 802. In this example, the electro-optic display layer 260 may have a portion having a microcell 607 and another portion 1315 that is substantially flat and configured to establish a connection with the piezoelectric material layer 802. In this configuration, the piezoelectric material layer 802 is arranged to overlap on the substantially flat portion 1315, ensuring a good connection with the electro-optic material layer 260. This configuration can advantageously establish a strong connection between the piezoelectric material layer 802 and the electro-optic material layer 260. For example, this configuration provides a strong connection between the piezoelectric material layer 802 and the electro-optic material layer 260, which can withstand repeated bending or stress applied to the electro-optic display 1300. In addition, an adhesive layer 240 may also be placed between the piezoelectric material layer 802 and the first light-transmitting electrode layer 210. Each microcell 607 includes an opening, and the sealing layer 230 spans each microcell opening. Furthermore, the second electrode layer 250 is adjacent to the electro-optic material layer 260. The second electrode layer 250 is disposed between the substrate 1316 and the electro-optic material layer 260.
[0098] exist Figure 8 ,9 In the electro-optical display examples illustrated in 10, 11, 12 and 13, the sealing layer is waterproof. The sealing layer comprises 40 to 95 weight % of polyvinyl alcohol, which contains acetoacetate functional groups in its molecular structure, based on the weight of the sealing layer excluding the solvent; and 5 to 60 weight % of polyurethane, based on the weight of the sealing layer excluding the solvent.
[0099] Electrophoresis medium
[0100] In the context of the present invention, electrophoretic medium refers to the composition in the microcell. For display applications, the microcell can be filled with at least one type of charged pigment particles in a non-polar fluid. The electrophoretic medium can contain one type of charged particles or more than one type of particles with different colors, charges and charge polarities. Under the influence of the electric field applied across the electro-optical material layer, the charged particles move through the electrophoretic medium. The charged particles can be inorganic or organic pigments, which have a polymer surface treatment that improves their stability. The electrophoretic medium can contain pigments with white, black, cyan, magenta, yellow, blue, green, red and other colors. The electrophoretic medium can also contain charge control agents, charge adjuvants, rheology modifiers and other additives. Examples of nonpolar fluids include hydrocarbons such as Isopar, decaline (DECALIN), 5-ethylidene-2-norbornene, fatty oils, paraffin oils, silicone fluids, aromatic hydrocarbons such as toluene, xylene, phenylxylylethane, dodecylbenzene or alkylnaphthalene, halogenated solvents such as perfluorodecalin, perfluorotoluene, perfluoroxylene, dichlorobenzotrifluoride, 3,4,5-trichlorobenzotrifluoride, chloropentafluorobenzene, dichlorononane or pentachlorobenzene, and perfluorinated solvents such as FC-43, FC-70 or FC-5060 from 3M Company, St. Paul MN, low molecular weight halogen-containing polymers such as poly(perfluoropropylene oxide) from TCI America, Portland, Oregon, poly(chlorotrifluoroethylene) such as Halocarbon Oils from Halocarbon Product Corp., River Edge, NJ, perfluoropolyalkyl ethers such as Galden from Ausimont or Krytox Oils and Greases from DuPont, Delaware K-Fluid Series, polydimethylsiloxane-based silicone oil (DC-200) from Dow-corning.
[0101] The electrophoretic medium may include two or more types of charged particles. The electrophoretic medium may include four types of charged particles, namely, first, second, third and fourth types of charged particles. The first, second, third and fourth types of charged particles may include first, second, third and fourth types of pigments, which have first, second, third and fourth colors, respectively. The first, second, third and fourth colors may be different from each other. The first type of particles may include inorganic pigments and have a first charge polarity. The second and third types of particles may have a second charge polarity opposite to the second charge polarity. The fourth type of particles may have a first charge polarity or a second charge polarity. The first type of particles may be white. The second, third and fourth charged particles may have a color selected from cyan, magenta and yellow.
[0102] Sealing layer
[0103] The sealing layer must provide a barrier to the electrophoretic medium so that the non-polar fluid will not move out of the multiple microcells. In addition, because the sealing layer contacts the electrophoretic medium and seals it within the microcavity, the sealing layer must (1) be almost insoluble in the non-polar fluid of the electrophoretic medium, and (2) have good barrier properties to the non-polar fluid so that the non-polar fluid does not diffuse out of the microcells during the life of the device. The poor barrier properties of the sealing layer to the non-polar fluid result in a reduction in the fluid from the electrophoretic medium and cause the sealing layer to sag. In certain applications, the sealing layer also needs to be waterproof where the electrophoretic device may be exposed to harsh conditions such as exposure to water or even insertion into water. In other words, the sealing layer must be elastic in water and must protect the electrophoretic medium under such conditions. The sealing layer must not negatively affect the electro-optical performance of the device.
[0104] The inventors of the present invention have found that a sealing layer comprising a combination of polyvinyl alcohol and polyurethane provides such benefits, the polyvinyl alcohol containing acetoacetate functional groups in its molecular structure.The polyvinyl alcohol used to form the sealing layer may be water soluble.
[0105] An example of a polyvinyl alcohol containing an acetoacetate functional group in its molecular structure is GOHSENX supplied by Mitsubishi Chemical. TM Z-410. This material is cross-linkable, and it can be cross-linked by heat treatment or exposure to ultraviolet radiation. Other commercially available examples of polyvinyl alcohols containing acetoacetate functional groups in their molecular structure include GOHSENX TM Z-100, GOHSENX TM Z-200, GOHSENX TM Z-205, GOHSENX TM Z-210, GOHSENX TMZ-220, GOHSENX TM Z-300 and GOHSENX TM Z-320. The polyvinyl alcohol may be a copolymer formed by polymerization of vinyl alcohol and vinyl acetoacetate. The polyvinyl alcohol may be a terpolymer formed by polymerization of vinyl alcohol, vinyl acetate and vinyl acetoacetate. The sealing layer comprises 40% to 95% by weight of the polyvinyl alcohol, the polyvinyl alcohol containing acetoacetate functional groups in its molecular structure, based on the weight of the sealing layer excluding the solvent. The sealing layer may comprise 45% to 93% by weight, or 50% to 90% by weight, or 55% to 85% by weight, or 60% to 80% by weight, or 65% to 78% by weight of the polyvinyl alcohol, the polyvinyl alcohol containing acetoacetate functional groups in its molecular structure, based on the weight of the sealing layer excluding the solvent. The degree of hydrolysis of the polyvinyl alcohol containing acetoacetate functional groups in its molecular structure may be 90% to 99%, or 91% to 98%, or 92% to 96%. The number average molecular weight of the polyvinyl alcohol containing acetoacetate functional groups in its molecular structure can be 1000 to 1000000 Dalton, or 10000 to 800000 Dalton, or 20000 to 700000 Dalton, or 40000 to 600000 Dalton. The polyvinyl alcohol of the sealing layer can be cross-linked. Cross-linked polyvinyl alcohol can be formed by the reaction of a cross-linking agent with an initial (non-cross-linked) polyvinyl alcohol. The cross-linking reaction can occur at the hydroxyl group or acetoacetate functional group of polyvinyl alcohol. The cross-linking agent reacts with two or more polyvinyl alcohol polymer molecules to form a bond between polymers. The bond can be a covalent bond. The cross-linking agent can have two or more reactive functional groups such as alcohol, amine and aldehyde. Non-limiting general examples of cross-linking agent categories include diamines, polyamines, diols, polyols, dialdehydes, dihydrazides, organic titanates, organic zirconates and organic borates. The cross-linking agent can be a saturated dialdehyde such as glyoxal with 2 to 6 carbon atoms. Other examples of polyvinyl alcohol crosslinking agents include methoxylenediamine, 1,3-bis(aminomethyl)cyclohexane, adipoyl dihydrazide, ZrO(OH)Cl·nH2O, (NH4)2ZrO(CO3)2, Sequarez 755, and Safelink™ SPM-01.
[0106] The cross-linked polyvinyl alcohol containing acetoacetate functional groups in its molecular structure can be formed from a cross-linkable polyvinyl alcohol and a cross-linking agent. The shelf life of the cross-linking agent exceeds 1 day. The shelf life of the cross-linking agent can exceed 2 days, more than 3 days, more than 5 days or more than 7 days.
[0107] The sealing layer of the present invention comprises 5% to 60% by weight of polyurethane by weight of the sealing layer excluding solvent. The sealing layer may comprise 10% to 55% by weight, or 15% to 50% by weight, or 18% to 45% by weight, or 20% to 40% by weight, or 22% to 35% by weight of polyurethane by weight of the sealing layer excluding solvent. The polyurethane may be an ester polyurethane or a polycarbonate polyurethane. The number average molecular weight of the polyurethane may be 1000 to 2000000 Daltons, 5000 to 1500000 Daltons, 10000 to 1000000 Daltons, or 30000 to 800000 Daltons. The polyurethane of the sealing layer may be crosslinked. The crosslinked polyurethane may be formed by crosslinking a crosslinking agent to a crosslinkable polyurethane. The crosslinking agent may be a polyisocyanate, a polyfunctional polycarbodiimide, a polyfunctional aziridine, a silane coupling agent, a boron / titanium / zirconium-based crosslinking agent, or melamine formaldehyde. The polyvinyl alcohol and the polyurethane of the same sealing layer can both be cross-linked.
[0108] Polyurethane is generally prepared by addition polymerization methods involving diisocyanates. Non-limiting examples of polyurethane include polyether polyurethane, polyester polyurethane, polycarbonate polyurethane, polyether polyurea, polyurea, polyester polyurea, polyester polyurea, polyisocyanate (e.g., polyurethane comprising isocyanate bonds) and polycarbodiimide (e.g., polyurethane comprising carbodiimide bonds). Typically, polyurethane contains urethane groups. The polyurethane used in the aqueous sealing composition and sealing layer described herein can be prepared using methods known in the art. Preferably, the polyurethane in the aqueous sealing composition and sealing layer of the present invention is polyester polyurethane, polycarbonate polyurethane and mixtures thereof.
[0109] The polyurethane of the sealing layer of the present invention can have a high degree of crystallinity, as measured by X-ray diffraction methods (XRD). Generally, polyurethane has a segmented structure. In other words, the hard segment comes from the isocyanate component (or chain extender, if present), and the soft segment comes from the diol (or polyol) component. The properties and molecular structure of the monomers used for polyurethane synthesis play a key role in the properties of the hard and soft segments. Generally, the crystallinity of the polyurethane can be controlled by the selection of the diol (or polyol) monomer.
[0110] The inventors of the present invention have observed that the use of polyurethanes with specific melting characteristics shows improved water resistance of the corresponding sealing layer. Specifically, polyurethanes with a peak melting temperature (Tm) of 115°C and above and a crystallinity index (Ic) of 8% and above show improved water resistance. The peak melting temperature (Tm) and the crystallinity index (Ic) are measured by differential scanning calorimetry (DSC). The DSC method involves raising the temperature of the polyurethane sample from 30°C to 220°C at a rate of 10°C. The heat flow at different temperatures is measured. The lowest point of the relationship line of heat flow (in W / g) relative to temperature is the peak melting temperature (Tm). The area in the figure (between the baseline and the heat flow line) corresponds to the melting enthalpy (expressed in J / g). The crystallinity index (Ic) is determined as the ratio of (A1 / A) multiplied by 100, where A is the area between the baseline and the heat flow line. Area A1 corresponds to the area below the peak melting temperature in the graph, and is defined by a straight line connecting the lowest point of the graph (corresponding to the peak melting temperature) and the baseline point corresponding to the onset temperature.
[0111] The sealing layer may comprise a weight ratio of polyvinyl alcohol to polyurethane of 19 to 0.7, or 15 to 0.8, or 10 to 1, or 8 to 1.5, or 5 to 2.
[0112] The sealing layer of the present invention may further include a surfactant. The aqueous sealing composition (and the corresponding sealing layer) may also include a wetting agent, also referred to as a surfactant. Examples of wetting agents include FC surfactants from 3M, Zonyl fluorinated surfactants from DuPont, fluoroacrylates, fluoromethacrylates, fluorinated long-chain alcohols, perfluorinated long-chain carboxylic acids and their derivatives and Silwet organosiloxane surfactants from OSi, Greenwich, Conn. The wetting agent can increase the affinity between the sealing layer and the microunit, increase the interfacial area between them, and improve the adhesion of the sealing layer to the microunit, providing a more flexible coating process. The surfactant may be an acetylenic diol. Non-limiting examples of acetylenic diols are 7,10-dimethyl-8-hexadecene-7,10-diol, 4,7-dimethyl-5-decene-4,7-diol, 2,4,7,9-tetramethyl-5-decene-4,7-diol and 3,6-dimethyl-4-octyne-3,6-diol. Commercial products of acetylenic diols include DYNOL TM 607、DYNOL TM 604, 104. 465, 440, 485, 2502 and FS-85. DYNOL TM and The surfactant is provided by Evonik. The surfactant can be an organosiloxane surface tension reducer such as provided by Momentive L-7607.
[0113] The sealing layer may be formed from an aqueous sealing composition. The aqueous sealing composition may include: (i) 40 to 95 wt% of polyvinyl alcohol, the polyvinyl alcohol containing acetoacetate functional groups in its molecular structure, based on the weight of the aqueous sealing composition excluding the solvent; and (ii) 5 to 60 wt% of polyurethane, based on the weight of the aqueous sealing composition excluding the solvent, and (iii) an aqueous carrier.
[0114] The aqueous sealing composition may comprise 5 to 98 wt %, or 10 to 90 wt %, or 15 to 80 wt %, or 20 to 70 wt %, or 25 to 60 wt % of the aqueous carrier, based on the weight of the aqueous sealing composition.
[0115] The application, drying or curing of the aqueous sealing composition forms a sealing layer. After drying or curing, the sealing layer may have some residual water and other solvents remaining in the sealing layer.
[0116] The polyurethane may be added to the aqueous sealing composition in the form of an aqueous solution or dispersion or an aqueous emulsion or latex.
[0117] The aqueous sealing composition may contain 0.5 to 10 weight % of a polyurethane crosslinking agent based on the weight of the aqueous sealing composition excluding the solvent. The polyurethane crosslinking agent forms a chemical bond between the polyurethane of the aqueous sealing composition and the polymer molecules of the microunit, increasing the adhesion between the sealing layer and the microunit. The polyurethane crosslinking agent is preferably soluble or dispersible in the aqueous carrier of the sealing composition. The polyurethane crosslinking agent can be a monomer, an oligomer or a polymer. Examples of polyurethane crosslinking agents include polyisocyanates, polyfunctional polycarbodiimides, polyfunctional aziridines, silane coupling agents, boron / titanium / zirconium-based crosslinking agents or melamine formaldehyde. The polycarbodiimide crosslinking agent is reactive under acidic pH conditions. Preferably, the crosslinking agent does not contain a sulfosuccinate surfactant.
[0118] The aqueous sealing composition may include 0.1 to 10 wt % of the polyvinyl alcohol cross-linking agent, based on the weight of the aqueous sealing composition excluding the solvent.
[0119] The aqueous sealing composition is prepared by mixing the ingredients in an aqueous carrier. The aqueous sealing composition can be applied to an appropriate surface to form a sealing layer. The aqueous sealing composition can be used to form a sealing layer immediately after its preparation, or more generally a few hours or days after its preparation to form a sealing layer. When the aqueous sealing composition needs to be stored for a period of time before its use, it is necessary to pay attention to obtaining an aqueous sealing composition that is stable over time. For example, the aqueous sealing composition must be a fluid with a viscosity that is low enough so that it can be successfully applied to form a sealing layer. This means that the aqueous sealing composition must have a sufficiently long shelf life. In some cases, the polyvinyl alcohol crosslinker, if present, can cause the viscosity of the aqueous sealing composition to increase to a level that prevents its use to form a sealing layer. Therefore, it is necessary to pay attention to the use of a polyvinyl alcohol crosslinker that causes the aqueous composition to have a sufficiently long shelf life. The shelf life of the aqueous sealing composition may exceed 1 day, exceed 3 days, exceed 5 days or exceed 7 days. Non-limiting examples of polyvinyl alcohol crosslinkers that provide long pot life include Safelink™ SPM-01 provided by Mitsubishi Chemical, glyoxal, and organic zirconates such as ZrO(OH)Cl*nH2O (provided as ZIRCOZOL ZC-2 by Daiichi Kigenso Kagaku Kogyo Co., Ltd) and (NH4)2ZrO(CO3)2 (provided as ZIRCOZOL AC-7 by Daiichi Kigenso Kagaku Kogyo Co., Ltd).
[0120] The aqueous sealing composition may also include a pH adjuster. The pH adjuster is added to the aqueous sealing composition to adjust its pH to a value of 6.5 to 8.5. An example of a pH adjuster is ammonium hydroxide, but various acids and bases may be used. The pH adjuster increases the pH of the aqueous sealing composition, which may reduce the crosslinking rate of the aqueous sealing composition before its use and provide optimal pH conditions for the rheology modifier to interact with the particles of the aqueous sealing composition, improving its efficacy. The pH adjuster may be used in an amount of 0.2 to 1 wt % based on the weight of the sealing composition excluding the solvent.
[0121] The aqueous sealing composition (and the resulting sealing layer) may also contain 0.05 to 10 wt %, or 0.1 to 5 wt %, or 0.5 to 2 wt % of a rheology modifier, based on the weight of the aqueous sealing composition (and the corresponding sealing layer) excluding the solvent. The rheology modifier increases the stability of the aqueous sealing composition during its storage. It also helps film formation, improves seal stability and provides other functions. Examples include associative thickeners, alkali swellable acrylic emulsions and other polymer thickeners. The aqueous sealing composition may contain a hydrophobically modified alkali swellable acrylic emulsion as a rheology modifier, such as Solthix provided by Lubrizol.TM A-100. The aqueous sealing composition may be shear thinning, that is, its viscosity decreases under higher shear. For example, the rheological profile of the aqueous sealing composition may show a viscosity of 10 -4 The viscosity at a shear rate of l / s and at a shear rate of 10 2 The viscosity at a shear rate of 1 / s is reduced by 5 to 10,000 times.
[0122] These and other aspects of the present invention will be further understood upon consideration of the following examples, which are intended to illustrate certain specific embodiments of the invention and are not intended to limit the scope of the invention as defined by the claims. Example
[0123] Water-sealing composition and evaluation method of sealing layer
[0124] A. Preparation Example of an aqueous sealing composition for forming a sealing layer.
[0125] Preparation example of water-based sealing composition. In a container, an aqueous polyurethane dispersion is combined with an aqueous solution of a surfactant and polyvinyl alcohol. Use a Hei-Torque Value 200 overhead mixer to mix the dispersion at 90rpm for 10 minutes. Then, add an appropriate amount of polyurethane crosslinking agent, add an appropriate amount of polyvinyl alcohol crosslinking agent, and mix the dispersion at 90rpm for another 60 minutes. Then use ammonium hydroxide to adjust the pH to 6.5-8.5 and mix the dispersion for another 30 minutes. Add an appropriate amount of rheology modifier to the dispersion and continue to mix for another 60 minutes. Then, degas the dispersion under reduced pressure (25mmHg) for 5 days. The obtained water-based sealing composition is used to prepare the sealing layer of the corresponding display.
[0126] B. Examples of sealing layers prepared using the drawdown method.
[0127] The aqueous sealing composition prepared in A above was coated on the indium tin oxide (ITO) side of the ITO-PET film using a Gardco drop coater. A gap of 15 mils and an eight-way square coater were used. The drop rate was set to 2 meters per minute to target a dry film thickness of 30 + / - 2 μm. The coating was dried in an oven at 100°C for 15 minutes. The dried film was conditioned at 25°C and 55% relative humidity (RH) for 24 hours.
[0128] C. Evaluation of the barrier properties of the sealant layer against non-polar fluids.
[0129] Using the aqueous composition prepared in Part A above, form Fig.14AThe sealing layer of the illustrated display 1400. The sealing layer is formed by the method described in B above. The display 1400 includes, in order: a substrate 1403, a first light-transmitting electrode layer 210 (conductive layer), a bottom layer 1405, a microcell layer 220 and a sealing layer 230. The microcell contains an electrophoretic medium containing pigment particles in Isopar E. The device 1400 is stored at 70°C for at least 24 hours. After this period of time, the electro-optical display is examined using an optical microscope for sagging of the sealing film due to loss of non-polar fluid of the electrophoretic medium. If the distance between the bottom of the microcavity being inspected and the lowest point of the bottom surface of the sealing layer is less than 85% of the distance between the bottom of the microcavity being inspected and the highest point of the lower surface of the sealing layer at the same microcell, the sealing layer is marked as "failed" for its barrier properties. Otherwise, that is, if the distance between the bottom of the microcell being inspected and the lowest point of the sealing layer is 85% or more of the distance between the bottom of the microcell being inspected and the highest point of the bottom surface of the sealing layer at the microcell being inspected, the sealing layer is marked as "passed" for its barrier properties. The barrier properties can also be evaluated qualitatively by observing the prepared electro-optical device with an optical microscope from the viewing side of the display. Displays containing a sealant layer that sags severely have a significantly different appearance (non-uniform surface versus uniform surface) than devices containing a sealant layer that has good barrier properties to non-polar fluids. For example, a display having a sealant layer having a sagging appearance may have a significantly different appearance (non-uniform surface versus uniform surface). Fig.15A The micro-units of the sealing layer that looks uniform are different from those with Fig. 15B The microcells shown are in contrast to the sealed microcells which appear to be non-uniform.
[0130] D. Preparation of electro-optical displays.
[0131] The electro-optical device was prepared by filling a plurality of microcells with a mixture of charged pigment particles (white, black and red) in Isopar E and then coating with an aqueous sealing composition as described in B above. Fig. 14B The illustrated display is constructed. The electro-optical display 1450 includes, in sequence: a protective film 1451, an optically transparent first adhesive layer 1452, a substrate 1403, a first light-transmitting electrode layer 210 (conductive layer), a bottom layer 1405, a micro-unit layer 220, a sealing layer 230, a second adhesive layer 240, an ITO electrode layer 1455, and a glass layer 1460. The electric field source 1461 electrically connects the first light-transmitting electrode layer 210 (conductive layer) to the ITO electrode layer 1455. The thickness of the first light-transmitting layer 210 is about 25 μm. The thickness of the substrate 1453 is about 100 μm. The thickness of the bottom layer 1405 is about 0.4 μm. The micro-unit layer 220 includes a plurality of micro-units. The bottom thickness of each micro-unit is about 0.4 μm and the height is about 14 μm. The thickness of the sealing layer 230 is about 10 μm, and the thickness of the second adhesive layer is about 6 μm.
[0132] E. Evaluation of the waterproofness of the sealing layer.
[0133] E1. The electro-optical display prepared in D above was switched to its red state and then immersed in a beaker containing water at a neutral pH of 25° C. for 2 hours. After this period, the display was removed from the beaker and visually inspected.
[0134] E2. The electro-optical display prepared in D above was switched to its red state and then immersed in a beaker containing water at a neutral pH of 100° C. for 15 minutes. After this period, the display was removed from the beaker and visually inspected.
[0135] The electro-optical display was tested for water resistance. After the electro-optical display was removed from the beaker, the display was rated as pass or fail by visual inspection according to the following criteria:
[0136] Failure: The display's sealant peels away from adjacent layers, the sealant includes cracks, or the display has a visual change in color compared to the same display prior to immersion in water.
[0137] PASS: The sealing layer of the display does not have portions that have peeled away from adjacent layers, the sealing layer does not include cracks, and the color of the display has no visual change compared to the same display prior to being submerged in water.
[0138] F. Evaluation methods of electro-optical performance.
[0139] The electro-optical performance of the display prepared by the above method B was switched to the white state, and the color of the white state was measured using a color computer (spectrophotometer i1, provided by x-rite). The display was switched to its red state, and the color of the red state was measured using a color computer (spectrophotometer i1, provided by x-rite). The results for each color state (white and red) were reported using CIELab color space values (L*, a*, and b*).
[0140] G. Evaluation of Peak Melting Temperature and Crystallinity Index of Polyurethanes by Differential Scanning Calorimetry.
[0141] A known mass of polyurethane is placed in a differential scanning calorimetry pot and the pot is sealed with a differential scanning calorimetry cover. Using a differential scanning calorimeter TA DSC25 provided by TA Instruments, the sample is heated from 30°C to 220°C at a rate of 10°C. A graph of normalized heat flow (in W / g) versus temperature is generated. The lowest point P of the graph is the peak melting temperature. The graph area (A) between the baseline and the normalized heat flow line is determined. Area A corresponds to the melting enthalpy. Draw a straight line from point P in the graph corresponding to the peak melting temperature to point B at the baseline at the starting temperature. The straight line (PB) divides area A into area A1 and area A2. Area A1 corresponds to the area below the peak melting temperature, and area A2 corresponds to the area above the peak melting temperature. The crystallinity index is the ratio of A1 / A multiplied by 100. In other words, Ic=100*(A1 / A).
[0142] Evaluation results
[0143] Unless otherwise indicated, the amounts of ingredients in the disclosed compositions are on a dry basis (excluding solvent). The term QS (sufficient amount) is used in some compositions to indicate the amount of carrier. This means that the amount of the ingredient in the composition is as much as is required to make the composition 100%, but not more.
[0144] Several aqueous sealing compositions were prepared by the general method described above in A. The prepared compositions are provided in Table 1.
[0145] Table 1 : Aqueous sealing composition. The content is the weight percentage of the ingredient based on the weight of the total composition (including the water carrier).
[0146]
[0147] Table 2 summarizes the sealant compositions, which are formed using the compositions of Table 1. In other words, sealant composition Comparative Example 1S is formed from the aqueous sealant composition from Comparative Example 1, sealant composition Comparative Example 2S is formed from the aqueous sealant composition from Comparative Example 2, sealant composition Example 3S is formed from the aqueous sealant composition from Example 3 (present invention), and sealant composition Example 4S is formed from the aqueous sealant composition from Example 4 (present invention). The content is the weight percentage of the ingredient based on the weight of the composition excluding the water carrier (and other residual solvents). In other words, sealant composition Comparative Example 1S is formed from the aqueous sealant composition from Comparative Example 1, sealant composition Comparative Example 2S is formed from the aqueous sealant composition from Comparative Example 2, sealant composition Example 3S is formed from the aqueous sealant composition from Example 3 (present invention), sealant composition Example 4S is formed from the aqueous sealant composition from Example 4 (present invention), and sealant composition Example 5S is formed from the aqueous sealant composition from Example 5 (present invention). The physical properties of the polyurethanes in the examples were determined by the methods described in Method G above.
[0148] Table 2 : Sealing composition. The content is the weight percentage of the ingredient based on the weight of the total composition.
[0149]
[0150] Information on the materials of the compositions provided in Tables 1 and 2: [1] GOHSENX provided by Mitsubishi Chemical TM Z-410; degree of hydrolysis 98%; [2] poly(vinyl alcohol-co-ethylene) copolymer supplied by Kuraray; Exceval TM RS-1717; degree of hydrolysis 93%; ethylene content 8%; [3] polyurethane aqueous dispersion; HD2125 aqueous dispersion, supplied by Hauthaway, with a dispersion in water of 35%; [4] polyurethane aqueous dispersion (polyester); 386-03, provided by Chemtura Corp.; [5] provided by Stahl XL-701; [6] DYNOL provided by Evonik TM 604; [7] Solthix provided by Lubrizol TM A-100.
[0151] Table 3 provides the results of the evaluation of the electro-optical device comprising a sealing layer whose composition is provided in Table 2. The electro-optical display was prepared according to Method D above.
[0152] Table 3 : Results of the evaluation of barrier properties and water resistance of electro-optical displays comprising the sealing layer compositions from Table 2.
[0153]
[0154] The evaluation results provided in Table 3 show that compared with polyvinyl alcohol containing no acetoacetate functional groups such as Exceval TM Compared to the sealing layer of RS-1717 (Comparative Examples S1-S2), it comprises a combination of polyvinyl alcohol and polyurethane, wherein the polyvinyl alcohol contains acetoacetate functional groups, such as GOHSENX TM The sealant layers of Z-410, (Examples S3, S4 and S5) show better barrier properties to non-polar fluids and better water resistance at 25°C.
[0155] Compared to sealing layers containing a combination of polyvinyl alcohol and polyurethane, where the polyvinyl alcohol contains acetoacetate functional groups, such as GOHSENX TM Z-410, and the peak melting temperature of the polyurethane is less than 115°C and the crystallinity index is less than 8%, such as 386-03, a sealing layer comprising a combination of polyvinyl alcohol and polyurethane, wherein the polyvinyl alcohol contains acetoacetate functional groups, such as GOHSENX TM Z-410, and where the polyurethane has a peak melting temperature of 115°C and above and a crystallinity index of 8% and above, such as HD2125, show better water resistance at 100°C (Examples S2 and S3 vs. Example S5).
[0156] Table 4 summarizes the results of the evaluation of the electro-optical performance of electro-optical displays comprising sealing layers corresponding to Comparative Example 2S and Example 3S (invention). The data represent the color data of the white state and the red state of the corresponding electro-optical displays determined by Method F above.
[0157] Table 4: Electro-optical performance of electro-optical displays.
[0158]
[0159] The data of Table 4 show that the color behavior of electro-optical displays comprising sealing layers having compositions from Comparative Example 2S and Example 3S (invention) are very similar. In other words, the use of the sealing layer composition of the invention does not negatively affect the color behavior of the display.
Claims
1. A waterproof sealing layer, comprising: a. 40 to 95% by weight of the sealing layer excluding the solvent, polyvinyl alcohol, the polyvinyl alcohol containing acetoacetate functional groups in its molecular structure; and b. 5 to 60 wt % polyurethane based on the weight of the sealing layer excluding solvent.
2. The waterproof sealing layer according to claim 1, wherein: The polyurethane has a peak melting temperature of 115° C. and above and a crystallinity index of 8% and above.
3. The waterproof sealing layer according to claim 1, wherein: The polyurethane is cross-linked.
4. The waterproof sealing layer according to claim 3, wherein: The polyurethane is cross-linked by a cross-linking agent, and the cross-linking agent is polyisocyanate, multifunctional polycarbodiimide, multifunctional aziridine, silane coupling agent, boron / titanium / zirconium-based cross-linking agent or melamine formaldehyde.
5. The waterproof sealing layer according to claim 1, wherein: The polyvinyl alcohol is cross-linked.
6. The waterproof sealing layer according to claim 5, wherein: The cross-linked polyvinyl alcohol is formed by the reaction of polyvinyl alcohol and a cross-linking agent selected from the group consisting of dialdehydes and organozirconates.
7. The waterproof sealing layer according to claim 6, wherein: The cross-linking agent is selected from glyoxal, ZrO(OH)Cl*nH2O and (NH4)2ZrO(CO3)2.
8. The waterproof sealing layer of claim 1, further comprising a surfactant selected from the group consisting of acetylenic diols, organosiloxanes, and combinations thereof.
9. The waterproof sealing layer according to claim 1, wherein: The sealing layer is formed of an aqueous sealing composition.
10. The waterproof sealing layer according to claim 9, wherein: The aqueous sealing composition has a shelf life of more than 1 day.
11. The waterproof sealing layer according to claim 9, wherein: The aqueous sealing composition comprises a polyurethane dispersion.
12. The waterproof sealing layer according to claim 9, wherein: The number average molecular weight of the polyurethane is 1,000 to 2,000,000 Daltons.
13. The waterproof sealing layer according to claim 9, wherein: The number average molecular weight of the polyvinyl alcohol is 1,000 to 1,000,000 Daltons.
14. The waterproof sealing layer according to claim 9, wherein: The hydrolysis degree of the polyvinyl alcohol is 90% to 99%.
15. An electrophoretic display, comprising: a first light-transmitting electrode layer; an electro-optical material layer comprising a sealing layer according to claim 1 and a microcell layer comprising a plurality of microcells, each microcell in the plurality of microcells comprising a bottom, a wall and an opening, and containing an electrophoretic medium comprising at least one type of charged pigment particles dispersed in a non-polar fluid, wherein the sealing layer spans the openings of the plurality of microcells; The second electrode layer.
16. The electrophoretic display device according to claim 15, wherein: The polyurethane has a peak melting temperature of 115° C. and above and a crystallinity index of 8% and above.
17. The electrophoretic display device according to claim 15, wherein: The sealing layer is disposed between the micro unit layer and the second electrode layer.
18. The electrophoretic display device according to claim 15, wherein: The electrophoretic medium comprises four types of charged pigment particles, wherein colors of the four or more pigment particles are selected from white, magenta, yellow, cyan, blue, red, green and black.
19. The electrophoretic display device of claim 15, further comprising a piezoelectric material layer comprising a piezoelectric material, wherein: The piezoelectric material layer is arranged between the first light-transmitting electrode layer material and the electro-optical material layer or between the electro-optical material layer and the second electrode layer.
20. The electrophoretic display device according to claim 15, wherein: The electrophoretic display is used as an authentication element on an object selected from the group consisting of currency, stock certificates, bond certificates, negotiable instruments, debit cards, credit cards, receipts and smart cards.
